Determining the clinical relevance of outcomes for evaluating regular therapies for children with asthma—a survey of clinicians, parents and young people. (29th September 2015) - Sinha, I; Gallagher, R; Williamson, P; Smyth, R
Abstract : Background: Clinical trials of regular therapies for children with asthma frequently measure outcomes reflecting short-term disease activity, but rarely assess functional status, quality of life (QoL), and long-term treatment effects.1 There is a lack of research assessing the importance of outcomes for children with asthma, from the perspective of clinicians, parents and young people.2 The authors aimed to identify the outcomes of most importance to these groups. Methods: Paediatricians and specialist nurses, identified through the British Paediatric Respiratory Society, completed a two-round Delphi-survey. Parents, recruited in asthma clinics, participated in both rounds. Young people, 13 years or older, participated in the first round. Outcomes were considered for preschool and school-aged children separately. In Round 1, clinicians suggested important outcomes used in clinical practice. Parents and young people were asked how they judged whether they were satisfied with asthma medications. Responses were classified into corresponding outcomes by two researchers independently. In Round 2, participants were shown outcomes suggested by at least 10% of responders in Round 1. They scored the importance of each from 0–4, and selected the three most important. Results: Forty-six clinicians completed Round 1. Forty-three completed Round 2. Thirty-eight parents and eleven young people completed Round 1. Fifty parents completed Round 2. Eighteen outcomes were listed in Round 2. The most important outcomes for school-aged and preschool children reflected clinical measures of disease activity (symptoms and exacerbations), QoL, activities of daily living and long-term effects of treatments. The results from parents and clinicians were generally concordant, but parents placed more emphasis on long-term effects of treatments. Conclusion: Some outcomes which are rarely measured in clinical trials in children with asthma, namely, QoL, functional status and long-term effects of interventions, are very important to clinicians and parents of children with asthma. These outcomes should be measured in clinical trials. People involved in standardising outcomes for such trials should be aware of these findings.